The Administrative Skills of Head Teacher in Educational Institutions - Adhikari, Narayan Prasad; Budhathoki, Jhupa Kumari (International Research Journal of Parroha, 2023)
The objective of this study was to determine the administrative skills of head teachers in operating educational institutions. The study used the descriptive method to identify the key skills required for effective school leadership. The key method used in this study was the descriptive method, which involved identifying and describing the necessary administrative skills of head teachers. The study focused on three main skills: technical, interpersonal, and conceptual. These skills were deemed crucial and vital for organizing, leading, controlling, and planning in educational institutions. Head teachers must implement the knowledge and abilities that will improve the efficacy and efficiency of the school's teaching and learning. To maintain the effectiveness of their leadership positions and improve academic accomplishment among their students, it is advised that head teachers make the most use of their administrative competencies and capabilities. In order to improve the professionalism of teacher performance and ensure the success of education in schools, head teachers must possess and utilize the necessary administrative skills. These skills include technical, interpersonal, and conceptual abilities, which are crucial for organizing, leading, controlling, and planning. By effectively applying their administrative competencies and capabilities, head teachers can enhance the efficacy and efficiency of their schools' teaching and learning processes, ultimately leading to improved academic achievement among students.